COVID-19: A Brief Overview of the Discovery Clinical Trial - Jean Jacques Vanden Eynde (MDPI AG, 2020)
The outbreak of COVID-19 is leading to a tremendous search for curative treatments. The urgency of the situation favors a repurposing of active drugs but not only antivirals. This short communication focuses on four treatments recommended by WHO and included in the first clinical trial of the European Discovery project.